NIMROD modeling of quiescent H-mode: reconstruction considerations and saturation mechanism. (30th September 2016) - King, J.R.; Burrell, K.H.; Garofalo, A.M.; Groebner, R.J.; Kruger, S.E.; Pankin, A.Y.; Snyder, P.B.
Abstract: The extended-MHD NIMROD code (Sovinec and King 2010 J. Comput. Phys . 229 5803) models broadband-MHD activity from a reconstruction of a quiescent H-mode shot on the DIII-D tokamak (Luxon 2002 Nucl. Fusion 42 614). Computations with the reconstructed toroidal and poloidal ion flows exhibit low- n ϕ perturbations ( n ϕ ≃ 1 –5) that grow and saturate into a turbulent-like MHD state. The workflow used to project the reconstructed state onto the NIMROD basis functions re-solves the Grad–Shafranov equation and extrapolates profiles to include scrape-off-layer currents. Evaluation of the transport from the turbulent-like MHD state leads to a relaxation of the density and temperature profiles.